Software Piracy Scenario Among Diploma Students Majoring in Information Systems Engineering - Abdul Samad, Rosleen (2001)
Software piracy is a worldwide problem for the software industry. Malaysia too does not have the immunization for this disease. In trying to curb this problem it is best to understand the factors that influences individuals to pirate software or to purchase original software. As students will be the future leaders, this study main objective is to get the snapshot of the software piracy scenario of students. The target group for this study is on diploma students, majoring in Information Systems Engineering. The respondents are divided into two groups, the group that involve in software piracy activities and the group that does not indulge in software piracy activities. Findings of this study centers on the reasons for students to pirate software or to purchase original software. Comparisons on the reasons for purchasing original software between the two groups are presented too.